Eco-epidemiology of the tick Ixodes ricinus and of transmitted pathogens in Switzerland - (:unkn) unknown (My University, 2025)
In Switzerland, the most significant vector-borne diseases in humans are Lyme borreliosis (LB) and Tick-borne encephalitis (TBE), both transmitted by the tick Ixodes ricinus. LB, a systemic disease due to a bacteria, Borrelia burgdorferi sensu lato, exists in Europe, North America, Asia and North Africa. Tick-borne encephalitis (TBE) is a severe neurological disease caused by viruses which are widely distributed in northern Eurasia. Over this distribution, TBE virus is usually observed in distinct pockets of infection within forests, natural foci. Global climate change has been suspected in having potentially serious effects on geographical and temporal distributions of tick-borne diseases. We will study the dynamic of Lyme borreliosis and TBE foci in relation with climatic data and investigate the evolution of tick density, tick infection and host populations. Currently, Switzerland is facing two major problems in the epidemiology of TBE: an increase of TBE cases, in particular in 2005 and 2006, and the identification of TBE foci. In the present study, we intend to tackle these 2 problems. TBE areas where an increase in the number of clinical cases occurred these last years will be followed monthly over 3 years. Identification of TBE foci will also be performed in order to clarify the situation in the western part of Switzerland. I. ricinus may also carry a protozoa belonging to the genus Babesia inducing babesiosis in human and animals. In Europe, human babesiosis seems to be mainly due to B. divergens, a cattle parasite. Recently, a new Babesia species, Babesia sp. EU1, has been described in two asplenic patients, in Italy and in Austria. This species has been detected in I. ricinus in Switzerland and we intend to evaluate its prevalence in ticks, as well as to identify its reservoir hosts. Effect of parasite on the physiology of ticks is not well documented. In 1998, in Neuchâtel, desiccating conditions were high and questing tick density was very low. Examination of ticks showed that 84% of infected ticks were infected by a high load of spirochetes. One of the explanations for this could be that infection with B. burgdorferi makes ticks more resistant to heat and desiccation. We will test this hypothesis. The proposed project should contribute to a better understanding of the ecology and epidemiology of I. ricinus ticks and of tick-borne pathogens in Switzerland in relation with human risk to acquire the related diseases. Analysis of ticks collected in different areas in Switzerland for TBE virus should help to identify regions at risk where the frequency of clinical cases is too low to classify these areas as endemic areas for TBE. Identification of TBE foci would allow developing a strategy of prevention of TBE infection by vaccination indication. Exposure risk to pathogens responsible for emerging diseases, like Babesia sp EU1, will also be evaluated.
Keywords: borrelia burgdorferi; babesia sp; TBE virus; ixodes ricinus; phenology; climate change